LANGUAGE LEARNING AND DIDACTIC ACTIVITIES FOR SCHOOL CHILDREN (World Bulletin of Social Sciences, 2023)
Challenging yet pleasurable communicative approach promotes positive attitude toward the daily study in language learning. Pupils working in groups have comprehension activity, journal sharing, question discussion and roleplaying of the characters in the books or plays. Communicative approach not only lightens classroom anxiety but also promotes pupils cooperative learning and enhances their communication abilities.